Determining State’s Financial Losses in Corruption - Suta, I Made Gemet Dananjaya; Prabandari, I Gusti Agung Mas; Astariyani, Ni Luh Gede (Lentera Hukum, 2021)
One of the main elements in corruption is the loss of state finances. It results in confusion impacting law enforcement officials' performance in eradicating corruption. In Indonesia, the Supreme Audit Agency (BPK) is an institution authorized to assess state financial losses. In practice, the Financial and Development Supervisory Agency (BPKP) is another institution with similar power. This study analyzed which institutions have the more appropriate power in determining state financial losses in corruption. Using legal research with statutory and conceptual approaches, this study showed that the BPK is an institution granted the constitutional power to examine state finances' management and responsibility, asserting its more legitimate institution to handle the power to assess the financial losses. Consequently, the BPK is the only state institution that can determine state financial losses. At the same time, the BPKP is only authorized to assess or audit the calculation of state financial losses as an indication of irregularities detrimental to state finances. This study concluded that only the BPK can assess and determine state financial losses used in examining the alleged corruption before the court. KEYWORDS: Institutional Powers, Financial Audit Institution, Corruption.